Адская рулетка: [роман] / Леонид Влодавец - Влодавец Леонид Игоревич (Серия "Чёрная кошка", 1997)
Экземпляры: Аб (20141030) / Инвентарный номер: 101722 / Цена: 40.00 / Авт.знак: В 58 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6